miR396-OsGRFs Module Balances Growth and Rice Blast Disease-Resistance - Chandran, Viswanathan; Wang, He; Gao, Feng; Cao, Xiao-Long; Chen, Yun-Ping; Li, Guo-Bang; Zhu, Yong; Yang, Xue-Mei; Zhang, Ling-Li; Zhao, Zhi-Xue; Zhao, Jing-Hao; Wang, Ying-Ge; et al. (Frontiers in Plant Science, 2019)
Fitness cost is a common phenomenon in rice blast disease-resistance breeding. MiR396 is a highly conserved microRNA (miRNA) family targeting Growth Regulating Factor (OsGRF) genes. Mutation at the target site of miR396 in certain OsGRF gene or blocking miR396 expression leads to increased grain yield. Here we demonstrated that fitness cost can be trade-off in miR396-OsGRFs module via balancing growth and immunity against the blast fungus. The accumulation of miR396 isoforms was significantly increased in a susceptible accession, but fluctuated in a resistant accession upon infection of Magnaporthe oryzae. The transgenic lines over-expressing different miR396 isoforms were highly susceptible to M. oryzae. In contrast, overexpressing target mimicry of miR396 to block its function led to enhanced resistance to M. oryzae in addition to improved yield traits. Moreover, transgenic plants overexpressing OsGRF6, OsGRF7, OsGRF8 and OsGRF9 exhibited enhanced resistance to M. oryzae, but showed different alteration of growth. While overexpression of OsGRF7 led to defects in growth, overexpression of OsGRF6, OsGRF8 and OsGRF9 resulted in better or no significant change of yield traits. Collectively, our results indicate that miR396 negatively regulates rice blast disease- resistance via suppressing multiple OsGRFs, which in turn differentially control growth and yield. Therefore, miR396-OsGRFs could be a potential module to demolish fitness cost in rice blast disease-resistance breeding.